The potential of mitochondrial transfer as the modifying therapy for osteoarthritis - He, Yuanpei; Wang, Xinge; Xu, Boya; Chen, Shichao; Li, Hongcai; Chang, Bei; Hu, Chao; Lan, Xiaorong; Li, Shiting; Li, Guangwen (Frontiers in Cell and Developmental Biology, 2025)
Mitochondrial transfer is defined the process through which specific cell types release their mitochondria and subsequently transfer them to unrelated cell types in response to various physiological or pathological stimuli. This process enhances cellular function and alters disease states. Recent research has begun to explore the potential of intercellular mitochondrial transfer as a therapeutic strategy for human diseases. Mitochondrial dysfunction represents a significant pathological alteration in osteoarthritis, and studies indicate that mitochondrial transfer may serve as an effective modulatory treatment approach for osteoarthritis. Mitochondrial transfer, as an innovative subcellular therapeutic technique, presents the advantages of diverse acquisition methods and multiple transmission pathways. This paper aims to summarize the current understanding of the mechanisms of mitochondrial transfer in relation to osteoarthritis, emphasizing the existing research on mitochondrial transfer in osteoarthritis and its potential as a disease-modifying therapy.